Epidemiological Aspects of Visceral Leishmaniasis in Baft District, Kerman Province, Southeast of Iran - H Mahmoudvand; M Mohebali; I Sharifi; H Keshavarz; H Hajjaran; B Akhoundi; S Jahanbakhsh; M Zarean; A Javadi (Iranian Journal of Parasitology, 2011)
Background: Visceral leishmaniasis (kala-azar) is an endemic disease in some areas of Iran. A cross- sectional study was conducted for sero-epidemiological survey of visceral leishmaniasis (VL) in Baft district from Kerman Province, southeast of Iran.